Adaptation of Farmers in Rice Cultivation at Dry Season in Gunungsari Village (Bojonegoro-East Java) For Learning Source - Damhuri, Damhuri; Sejati, Andri Estining; Hidayati, Desi Nurul (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
Gunungsari is one of village in Bojonegoro located around the Solo River downstream. Farming areas experiencing water shortages because the monthly rainfall is always dry in dry season. Rice canât live without adequate water. That seasonal condition making farmers must think to get way to continuous rice cultivation. This paper aims to determine farmer adaptation in rice cultivation at dry season for raw data in the learning source. This research is survey with population 385 heads of family farmers. Samples were taken by proportional random sampling technique is 80. Collecting data use observation, interviews, and documentation. Data analyzed with descriptive quantitative, then information will develop in the learning source in the next research. The results that the form of adaptation, include: (1) farmers began planting in June when river water still available. (2) To hold water by way pumping river water to Solo River to secondary, pumped again to tertiary, then flowed to rice fields. (3) Farmers must set aside 16% of the yield to pay for pumping effort. This research result can become lecturer learning source both in Biology Education department and in Geography Education department. Biology Education is specially relating in the plant matter. Geography Education is specially relating in the agriculture geography matter. Development Learning Source for higher education must begin from research like this research. Learning source with information from the research can learn more contextual and easier to understand.